2017
DOI: 10.1007/s00415-017-8570-4
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital ischaemic stroke treated with intravenous thrombolysis or mechanical thrombectomy

Abstract: Patients with in-hospital strokes (IHS) may be eligible for recanalization therapies. The objective of this study is to compare outcomes in patients with IHS and community-onset strokes (COS) treated by recanalization therapy. We analysed data prospectively collected in consecutive patients treated by thrombolysis, thrombectomy, or both for cerebral ischemia at the Lille University Hospital. We compared four outcomes measures at 3 months in patients with IHS and COS: (1) modified Rankin scale (mRS) 0-1, (2) mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
3
24
2
Order By: Relevance
“…Given that there is a clear benefit of endovascular reperfusion therapies in patients with AIS with emergent large‐vessel occlusions, either with or without pre‐treatment with systemic thrombolysis , there is also an urge to increase in‐hospital awareness regarding endovascular reperfusion therapies as highly relevant treatment options in the setting of emergent large‐vessel occlusion and especially for patients with IHS who, due to prevalent comorbidities, might be ineligible for IVT. Notably, a recent French study reported markedly high mechanical thrombectomy treatment rates (45%) in a series of 64 patients with IHS .…”
Section: Discussionmentioning
confidence: 99%
“…Given that there is a clear benefit of endovascular reperfusion therapies in patients with AIS with emergent large‐vessel occlusions, either with or without pre‐treatment with systemic thrombolysis , there is also an urge to increase in‐hospital awareness regarding endovascular reperfusion therapies as highly relevant treatment options in the setting of emergent large‐vessel occlusion and especially for patients with IHS who, due to prevalent comorbidities, might be ineligible for IVT. Notably, a recent French study reported markedly high mechanical thrombectomy treatment rates (45%) in a series of 64 patients with IHS .…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings might be somehow misleading because not all patients with IHS were candidates for acute intervention. When only patients who had received acute intervention were considered, one study found an even faster onset to intravenous thrombolysis time among patients with IHS than among those with COS (128 vs 145 min, P < 0.001) [21]. Another study also demonstrated an improvement in assessment and treatment time after an IHS alert protocol was established in a single hospital [22].…”
Section: Discussionmentioning
confidence: 99%
“…4 In-hospital stroke patients are also less likely to ambulate at discharge and more likely to have higher modified Rankin scores. 2,6 Similarly, lengths of stay are higher for in-hospital strokes. Mean length of stay after community-onset stroke is 13 days compared with 21 days after in-hospital strokes.…”
Section: (I) Comparison Of Outcomes Between In-hospital Strokes and Cmentioning
confidence: 99%
“…Aside from recurrent strokes on stroke units, cardiology and cardiac surgery units are the most common locations for in-hospital strokes to occur. 6,7,9 Not surprisingly then, in-hospital stroke mechanism is more often embolic (cardioembolic or arteroembolic). 3 In a Canadian provincial prospective cohort study, almost half of in-hospital strokes occurred during admission for surgery and 15% of strokes occurred during angiography.…”
Section: (I) Comparison Of Outcomes Between In-hospital Strokes and Cmentioning
confidence: 99%
See 1 more Smart Citation